How to make friends with the dark - Glasgow, Kathleen, 1969- (Delacorte Press, 2019)
Tiger, sixteen, has been pushing away from her overprotective mother, but when her mother dies suddenly Tiger must learn to live when it feels she is surrounded by darkness.